Analisis Perlindungan Hukum pada Nasabah Bank Syariah - Haryanti, Peni (Program Studi Hukum Ekonomi Syariah, 2023)
This research is motivated by the growing financing problems faced by financial institutions, especially Sharia banking. The financing problems often lead to foreclosure which resulted in the loss of the parties. Bank Muamalat Indonesia is the first bank to use Islamic principles, and services in the form of kind of protection given to customers in overcoming the problems of financing problems. Next is BPR SYARIAH Artha Tanmiya Kediri an Islamic financial institution that is still relatively new, whether these institutions are able to apply the principles of a truly accordance with sharia. This study aims to understand the legal protection of customer collateral in Bank Muamalat Indonesia KCP. Tulungagung and Tanmiya BPR SYARIAH Artha Kediri. This is the kind of field research with a qualitative approach. Data collection methods used were interviews and documentation. While the data analysis technique uses a single data analysis and site traffic analysis. A single data analysis that each data from research sites, while data analysis is the analysis of site traffic from both locations were analyzed together. The legal protection collateral provided by BMI KCP. Tulungagung, given with regard to the interests of both parties, bank interests, and the interests of customers. Legal protection associated with moving goods guarantees less than the maximum because there are still differences between the position of collateral collateral collateral chattels with security rights. Guarantee of goods moving in BMI Indonesia KCP. Tulungagung only as additional collateral; Legal protection of collateral in BPR SYARIAH Artha Tanmiya Kediri done very maximum as collateral does not serve as a guarantee that will be sold in the event of financing problems. However, the guarantee on the BPR SYARIAH Artha Tanmiya Kediri is a bank guarantee that customers pay off financing to the restructuring of financing.